Nutrition and Digital Health Literacy Education for Parents of Children with Special Needs - Nurrohmah, Nisa; Rahmawati, Dwi Hayuni Kukuh; Mumtaz, Dera Haidar; Al Hima, Najwa Mathla'; Andrianto, Kevin Prasanna; Arindita, Ruvira (Universitas Padjadjaran, 2026)
Children with Special Needs (CSN/ABK) face complex nutritional risk due to sensory, motor, and medication challenges, yet parents and companion teachers often lack specific and credible nutrition literacy. This study aimed to evaluate the effectiveness of a digital health literacy-based nutrition education intervention in improving the nutrition knowledge of CSN parents and teachers. This study utilizes a quasi-experimental design without a control group (one-group pretest–posttest design) involving 30 participants, comprising parents and teachers at SLB Ulaka Penca, through a nutritional education approach known as the ENERGY (Education of Nutrition with Digital Literacy) program. The intervention was carried out over approximately three months, consisting of three educational sessions. Each session lasted for about 120 minutes and was delivered through field-based education integrated with digital media.The curriculum encompassed balanced nutrition for children with special needs, nutritional issues and requirements, the daily application of balanced nutrition, and the utilization of digital literacy, further reinforced by documentary videos. For the statistical analysis, knowledge data were processed using the Wilcoxon Signed Ranks Test, a non-parametric method necessitated by the non-normal distribution of the posttest data. The result shows that a significant increase in the average knowledge score was observed, rising from approx 55.00 to approx 85.00. The Wilcoxon test demonstrated a highly significant difference between pretest and posttest scores p = 0.000. The digital health literacy-based nutrition education intervention proved to be highly effective in improving nutrition knowledge. Utilizing easily accessible digital platforms (WhatsApp and digital booklets) is an appropriate strategy to bridge the gap in specialist nutrition information and ensure educational sustainability for CSN caregivers.Keywords: Children with special needs, digital health literacy, nutrition education.